2017
DOI: 10.1501/vetfak_0000002811
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage temperature on HMF and diastase activity of strained honeys

Abstract: Summary:This research intends to reveal the effects of different storage temperatures on the HMF amounts and diastase activities of strained flower honey and honeydew honey samples produced by different companies in Turkey. In this context, the initial HMF values and diastase activities of the strained flower honey and honeydew honey samples belonging to five different companies, collected at the date of filling, were examined with defined quality criteria (moisture, sugar, pH, acidity, electrical conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…According to the Turkish Food Codex Honey Communiqué, the number of diastases in flower honey should be 8 or more (Turkish Food Codex, 2020). In the thesis study conducted by Korkmaz and Küplülü (2017) they reported that the diastase number in five different flower honeys was between 10.8 and 14.1 on day zero. The number of diastase in honey analyzed in this study was measured between 17.0 and 18.8.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the Turkish Food Codex Honey Communiqué, the number of diastases in flower honey should be 8 or more (Turkish Food Codex, 2020). In the thesis study conducted by Korkmaz and Küplülü (2017) they reported that the diastase number in five different flower honeys was between 10.8 and 14.1 on day zero. The number of diastase in honey analyzed in this study was measured between 17.0 and 18.8.…”
Section: Resultsmentioning
confidence: 97%
“…HPLC-UV was calibrated with the solution of Hydroxymethylfurfural (HMF). Analyses were done by handling the C18-reversed-phase column below the isocratic mobile phase terms with the inclusion of 90% distilled water-10% methanol by a flow rate of 1 mL/min and the injection volume was 10 µL (Korkmaz & Küplülü, 2017). Diastase analyses of honey samples were identified by handling UV-Spectrophotometer (Shimadzu UV-1800, Japan), according to the method recommended by TSE method (TSE 3036, 2002).…”
Section: Analyzesmentioning
confidence: 99%